3D-printed electrochemical sensors - Siqueira, Gilvana P.; de Faria, Lucas V. [UNESP]; Swain, Krishna Kumari; Trindade, Magno A.G. [UNESP]; Richter, Eduardo M.; Muñoz, Rodrigo A.A. (Elsevier, 2025)
This chapter presents a preliminary background on 3D printing technologies applied for electrochemical applications, especially focusing electroanalysis. Next, we present a brief guide for those who intends to start working with 3D-printed electrodes for electroanalysis, pointing out how (a) to investigate such electrode processes toward electrochemical sensing, (b) protocols of surface posttreatment of 3D-printed electrodes, and (c) the influence of 3D printing parameters on the electrode processes. Next, the chapter will describe some applications of 3D-printed electrodes in different fields, including forensics, food, (bio)fuels, and natural water contaminants. The main analytical features of the proposed electroanalytical methods are discussed and presented in tables, which also show the photos or schemes of the 3D-printed devices. Finally, perspectives of 3D-printed electrochemical sensors are presented with future directions.
Keywords: Additive manufacturing; Biofuels; Carbon-based composite materials; Electrochemistry; Environmental analysis; Food; Forensic; Fused filament fabrication